Caracteristicas químico-bromatológicas de silagens de Capim elefante (Pennisetum purpureum schum) com diferentes níveis de inclusão de resíduo de fécula de mandioca - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The objective of this study was to evaluate the chemical composition of elephant grass silages (Pennisetum purpureum schum) with different levels of inclusion of cassava starch by-products. The forage used was elephant grass and after shredding that left it with 4mm, the material was manually compacted in experimental PVC silos. The design was completely randomized with five levels of inclusion of cassava starch by-products in natural matter (0%, 10%, 20%, 30% and 40%) with four replications. The silos were opened after 49 days fermentation. The inclusion of cassava starch by-products in elephant grass silages shows linear increment (P <0.01) without dry matter content (DM), which includes 10% of dry matter content (31.74%) within the range. optimal range (28 to 35%) for proper fermentation. Organic matter (OM) and mineral matter (MM) showed an inversely proportional relationship when the inclusion levels (94.45 to 97.48%) and (5.55 to 2.52%) increased from 0 to 40% of procedures, inclusion of by-product respectively. Non-nitrogenous extractives (NNE) showed linear increase, with content (77.25%) without treatment with 40% of inclusion. Nitrogen in digestible acid detergent (NIDA) and indigestible protein in acid detergent (PIDA) increased linearly (P <0.01) reaching maximum levels of 0.69 and 4.70% without further treatment, respectively. Total carbohydrates (CHOT), non-fibrous carbohydrates (CNF) and total digestible nutrients (TDN) experience increasing linear behavior (P <0.01) as levels increase (86.85 to 93.37%); (20.97 to 71.07%) and (58.23 to 74.24%) in the inclusions from 0 to 40%, respectively. A crude protein (CP) has no data shown (P <0.15). There was a linear decrease (P <0.01) in neutral detergent fiber (NDF), ether extract, crude fiber (FB), acid detergent fiber (FDA) and ammoniacal nitrogen (N-NH3) contents with lower value in investments. with 40% inclusion (22.21%; 16.17%; 19.43% and 0.52%), respectively. It is recommended to include 40% of cassava starch by-product.
Keywords: conservação de forragem; composição química; resíduo agroindustrial; CNPQ:: CIÊNCIAS AGRÁRIAS